Catalytic studies and trickle-bed reactor behaviour for wet oxidation of phenolic wastewaters : CFD and experimental analysis - Lopes, Rodrigo José Góis (2009)
Tese de doutoramento em Engenharia Química (Reactores Químicos) apresentada à Fac. de Ciências e Tecnologia da Universidade de Coimbra